Upaya Meningkatkan Inovasi Sociopreneurship Berdasarkan Program P2MW dalam Pengelolaan limbah Buah Kelapa sebagai Budidaya Bonsai Berbasis High Value Tanaman Hias - Riris Verdina Purbayani; Triya Nur Fadila; Awin Mulyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The Entrepreneurial Student Development Program (P2MW) is a program to strengthen the entrepreneurial ecosystem in higher education institutions held by the Directorate of Learning and Student Affairs (Belmawa) and the Directorate General of Higher Education, Research and Technology of the Republic of Indonesia (Ditjen Diktristek RI). This P2MW activity provides opportunities for students who already have business ideas to become entrepreneurs, by providing support through financing, development and coaching. This program has stages of selection and training (coaching) which are expected to have a positive impact on students starting to develop their knowledge and skills in becoming entrepreneurs. Students at the University of 17 August 1945 Surabaya have the opportunity to take part in this program with an innovative effort to use coconut tree waste to make high-value coconut bonsai ornamental plants based on Sociopreneurship to also support the government in the G20 Presidency program and have the same goals as several SGDS points. This P2MW is located on the 17 August 1945 Surabaya University campus as the beginning of the process of creating and developing innovative designs which will then be competed at the KMI EXPO 2023 National level which is located at Undiksha Bali.